Autoantibody status, neuroradiological and clinical findings in children with acute cerebellitis - Quack, Lisa; Glatter, S.; Wegener-Panzer, A.; Cleaveland, R.; Bertolini, A.; Endmayr, V.; Seidl, R.; Breu, M.; Wendel, E.; Schimmel, M.; Baumann, M.; Rauchenzauner, M.; et al. (European journal of paediatric neurology, 2023)
Background - Acute cerebellitis (AC) in children and adolescents is an inflammatory disease of the cerebellum due to viral or bacterial infections but also autoimmune-mediated processes. - Objective - To investigate the frequency of autoantibodies in serum and CSF as well as the neuroradiological features in children with AC. - Material and methods - Children presenting with symptoms suggestive of AC defined as acute/subacute onset of cerebellar symptoms and MRI evidence of cerebellar inflammation or additional CSF pleocytosis, positive oligoclonal bands (OCBs), and/or presence of autoantibodies in case of negative cerebellar MRI. Children fulfilling the above-mentioned criteria and a complete data set including clinical presentation, CSF studies, testing for neuronal/cerebellar and MOG antibodies as well as MRI scans performed at disease onset were eligible for this retrospective multicenter study. - Results - 36 patients fulfilled the inclusion criteria for AC (f:m = 14:22, median age 5.5 years). Ataxia was the most common cerebellar symptom present in 30/36 (83 %) in addition to dysmetria (15/36) or dysarthria (13/36). A substantial number of children (21/36) also had signs of encephalitis such as somnolence or seizures. In 10/36 (28 %) children the following autoantibodies (abs) were found: MOG-abs (n = 5) in serum, GFAPα-abs (n = 1) in CSF, GlyR-abs (n = 1) in CSF, mGluR1-abs (n = 1) in CSF and serum. In two further children, antibodies were detected only in serum (GlyR-abs, n = 1; GFAPα-abs, n = 1). MRI signal alterations in cerebellum were found in 30/36 children (83 %). Additional supra- and/or infratentorial lesions were present in 12/36 children, including all five children with MOG-abs. Outcome after a median follow-up of 3 months (range: 1 a 75) was favorable with an mRS ≤2 in 24/36 (67 %) after therapy. Antibody (ab)-positive children were significantly more likely to have a better outcome than ab-negative children (p = .022). - Conclusion - In nearly 30 % of children in our study with AC, a range of abs was found, underscoring that autoantibody testing in serum and CSF should be included in the work-up of a child with suspected AC. The detection of MOG-abs in AC does expand the MOGAD spectrum.
Online veröffentlicht am 20.10.2023
Gesehen am 23.04.2024